Pengaruh Pengetahuan Produk Bank Syariah Terhadap Minat Menabung Mahasiswa Uin Sultan Maulana Hasanuddin Banten - Syifa, Dhe Salsabila; Puspita, Cici; Maulana, Dika; Saraswati, Henny; Sudrajat, Budi; Hidayat, Wahyu (Maisyatuna, 2023)
In order to increase public interest in using products from Islamic banking, Islamic financial institutions are obliged to increase the variety and quality of services and the variety of products offered. Involving students is one approach to growing the market share of the Islamic finance sector in Indonesia. so that it can learn which qualities Islamic financial institutions want to take into account. The problem in this study is whether product knowledge has an impact on consumer intentions to use Islamic banks. In this study, Islamic banking study program students in Banten used quantitative descriptive data from primary and secondary data sources collected by sending questionnaires to 33 respondents and using regression analysis techniques. specifically for students enrolled in the Islamic Banking Study Program, University of Sultan Maulana Hasanuddin Batch 2020–2023. The findings of this study indicate that product knowledge (P) influences the intention to use Islamic banks as customers (M).